2004
DOI: 10.1002/jcla.20044
|View full text |Cite
|
Sign up to set email alerts
|

Five polymorphisms in gene candidates for cardiovascular disease in Afro‐Brazilian individuals

Abstract: Associations of polymorphisms in the angiotensin I-converting enzyme (ACE), apolipoprotein B (APOB) and apolipoprotein E (APOE) genes with hypertension and variations in lipid serum levels were evaluated in 184 Afro-Brazilians with a familial history of coronary artery disease (CAD). ACE (Ins/Del) and APOB (Ins/Del, XbaI, and EcoRI) and APOE (HhaI) polymorphisms were determined by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analyses on agarose, and polyacrylamide gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
4
21
0
4
Order By: Relevance
“…28 Therefore, under the ancient African environmental condition, which was arid and hot, the sodium and water retaining capacity was crucial, carrying D allele frequency could be favored, given that the higher the D allele frequency, the higher the activity of serum ACE level. 19,20 When each population reached their new location and settled down, they were subject to new different evolutionary forces, such as cold temperatures and humid surroundings, which likely became important selective forces after human out-of-Africa expansion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Therefore, under the ancient African environmental condition, which was arid and hot, the sodium and water retaining capacity was crucial, carrying D allele frequency could be favored, given that the higher the D allele frequency, the higher the activity of serum ACE level. 19,20 When each population reached their new location and settled down, they were subject to new different evolutionary forces, such as cold temperatures and humid surroundings, which likely became important selective forces after human out-of-Africa expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The most impressive case is the angiotensin-converting enzyme (ACE) gene with a common polymorphism represented by the insertion (I) or deletion (D) of a 287-bp AluYa5 element inside intron 16 on chromosome 17q23, 19 which is associated with many cardiocerebral vascular diseases (CVDs). 20,21 Moreover, studies on ACE I/D polymorphisms have indicated that the Alu insertions are shown to be absent from the genomes of a number of non-human primates, consistent with the rise in human genetic polymorphisms sometime after the human/African anthropoid divergence, 22 which suggests that D allele is the ancestral allele 23,24 and its evolutionary history could be used to provide evidence for the 'thrifty genotype' hypothesis. On the other hand, accumulating evidence has suggested that genetic susceptibility to CVD as well as salt avidity and cardiovascular reactivity are ancestral and were likely magnified during the early human evolution before the out-of-Africa expansion of anatomically modern humans [25][26][27] and it is due to diverse selection pressure during the out-of-Africa expansion that occurred 30 000-100 000 years ago, among which, the most important selection pressure was climate.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…9 Previous studies have shown an association of ApoE gene polymorphisms with variation serum concentrations, hypertension and risk of myocardial infarction. 10,11 Our results show the first evidence of an association of ACE and ApoE polymorphisms with myocardial perfusion and suggest that the proposed effect of the abovementioned polymorphisms may have important influence on early patient risk stratification.…”
Section: Introductionmentioning
confidence: 54%
“…Previous studies have shown an association of ApoE gene polymorphisms with variation serum concentrations, hypertension and risk of myocardial infarction. 10,11 It has been shown that individuals with the e2 allele had lower risk of myocardial infarction and higher in e4 carriers, with a decrease of e4 allele frequency across the countries from Northern to Southern Europe, which follows the gradient of coronary heart disease mortality rates. 11,37 These results are consistent with the findings from this study in which the e4 allele and its genotypes have priority among patients with moderate and severe abnormal myocardial perfusion.…”
Section: Discussionmentioning
confidence: 99%